SEMIOTIC ANALYSIS OF MOON KNIGHT EPISODE 5: ASYLUM USING PEIRCE'S THEORY OF SIGN - Aulia Haris Firstiyanti; Aswarini Sentana; Ratna Wulandari (Universitas Gunadarma, 2025)
This research presents a semiotic analysis in an episode of a television series, focusing on Episode 5 of Moon Knight, titled